2021
DOI: 10.1007/s00296-021-04813-7
|View full text |Cite
|
Sign up to set email alerts
|

YouTube as a source of information on gout: a quality analysis

Abstract: YouTube is a popular video-sharing platform commonly visited by patients and healthcare professionals for medical information. Gout is the most frequent cause of inflammatory arthritis in adults. However, the accuracy and quality of gout-related information on YouTube are not fully known. Thus, the aim of this study was to assess the reliability and quality of YouTube videos pertaining to gout. A YouTube search was conducted using the keywords “gout”, “gout arthritis”, “gout treatment”, and “gout diet”. Of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
105
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(136 citation statements)
references
References 34 publications
23
105
1
7
Order By: Relevance
“…In this study, it was found that the mean DISCERN score of ministry/ academic/hospital/physician channel videos was higher than the mean score of entertainment/individual channel videos. Similar to this study, Onder and Zengin (2021) reported that YouTube videos uploaded by academic institutions/professional organizations have a higher reliability score. Although there was no significant difference between the groups in terms of DISCERN score in the study of Demir et al (2021), Culha et al (2021) evaluated YouTube videos about pelvic floor muscle exercises, it was seen that quality and reliable information was shared by health professionals (nurses, physicians, physiotherapists) regardless of the branch, and it was reported that the "DISCERN" scores of the videos uploaded by health professionals were high.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In this study, it was found that the mean DISCERN score of ministry/ academic/hospital/physician channel videos was higher than the mean score of entertainment/individual channel videos. Similar to this study, Onder and Zengin (2021) reported that YouTube videos uploaded by academic institutions/professional organizations have a higher reliability score. Although there was no significant difference between the groups in terms of DISCERN score in the study of Demir et al (2021), Culha et al (2021) evaluated YouTube videos about pelvic floor muscle exercises, it was seen that quality and reliable information was shared by health professionals (nurses, physicians, physiotherapists) regardless of the branch, and it was reported that the "DISCERN" scores of the videos uploaded by health professionals were high.…”
Section: Discussionsupporting
confidence: 86%
“…It was found that DISCERN, GQS, and CCC mean scores of videos grouped as informative were significantly higher than videos grouped as misleading. Onder and Zengin (2021) analyzed YouTube videos about gout in their study and, similar to this study, reported that the DISCERN and GQS scores of videos grouped as useful were significantly higher. Yuksel and Cakmak (2020) analyzed YouTube videos about COVID-19 and pregnancy, and similar to this study, most of the videos were categorized as informative.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations